2021
DOI: 10.4314/as.v20i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of snail production to income status of snail farmers in Edo South, Edo State, Nigeria

Abstract: This study examined the contribution of snail production to the income status of snail farmers in Edo South Senatorial District, Edo State, Nigeria. The specific objectives of the study were to describe the socio-economic characteristics of snail producers, estimate the costs and returns of snail production in the study area, examine the effect of snail production on income of snail farmers and identify the constraints to the production of snail in the study area. A two-stage sampling proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The result shows that a good fraction of the farmers are literates and so can apply extension agent's innovation with little or no assistance. This result is in consonance with findings of Ahmadu et al (2021) that revealed the dominance of farming business by literate farmers. The average household size of the farmers was 7 persons, with most (36.88%) of them having between 7 -9 persons in their households.…”
Section: Personal Characteristics Of Farmerssupporting
confidence: 91%
See 1 more Smart Citation
“…The result shows that a good fraction of the farmers are literates and so can apply extension agent's innovation with little or no assistance. This result is in consonance with findings of Ahmadu et al (2021) that revealed the dominance of farming business by literate farmers. The average household size of the farmers was 7 persons, with most (36.88%) of them having between 7 -9 persons in their households.…”
Section: Personal Characteristics Of Farmerssupporting
confidence: 91%
“…The implication of the result is that the respondents have people to cater for and who in return can serve as a source of farm labour to them. Findings of Ahmadu et al (2021) were in agreement with this result, believing that they have people to cater for and can assist them also in farm work.…”
Section: Personal Characteristics Of Farmerssupporting
confidence: 81%
“…It is clear that the youths were indifferent to the negative statements of livestock agribusiness as means of livelihood. A grand mean of 7.07 out of 10 points indicated livestock entrepreneurship is positively perceived as a source of income and livelihood (Ahmadu et al, (2021).…”
Section: Perception Of Livestock Agribusiness Entrepreneurship As a S...mentioning
confidence: 99%